Compliance programmes in relation to antitrust. Study of the Spanish guide and other comparative law experiences María Flora Martín Moral - Martín Moral, María Flora (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This paper aims to compare the Spanish situation, before and after the CNMC Guide on compliance programmes in relation to antitrust, of 10 June 2020, with other experiences from comparative law and with the criteria followed by the European Commission. We pay special attention to the determination of the effectiveness requirements of compliance programmes and to their role in stablishing the amount of penalties.
Keywords: antitrust; compliance programmes; competition authority; penalty